Analysis of the humoral and cellular immune response after a full course of BNT162b2 anti-SARS-CoV-2 vaccine in cancer patients treated with PD-1/PD-L1 inhibitors with or without chemotherapy: an update after 6 months of follow-up - Lasagna, A.; Lilleri, D.; Agustoni, F.; Percivalle, E.; Borgetto, S.; Alessio, N.; Comolli, G.; Sarasini, A.; Bergami, F.; Sammartino, J.C.; Ferrari, A.; Zavaglio, F.; et al. (ESMO open, 2022)
The durability of immunogenicity of SARS-CoV-2 vaccination in cancer patients remains to be elucidated. We prospectively evaluated the immunogenicity of the vaccine in triggering both the humoral and the cell-mediated immune response in cancer patients treated with anti-programmed cell death protein 1/programmed death-ligand 1 with or without chemotherapy 6 months after BNT162b2 vaccine. In the previous study, 88 patients were enrolled, whereas the analyses below refer to the 60 patients still on immunotherapy at the time of the follow-up. According to previous SARS-CoV-2 exposure, patients were classified as SARS-CoV-2-naive (without previous SARS-CoV-2 exposure) and SARS-CoV-2-experienced (with previous SARS-CoV-2 infection). Neutralizing antibody (NT Ab) titer against the B.1.1 strain and total anti-spike immunoglobulin G concentration were quantified in serum samples. The enzyme-linked immunosorbent spot assay was used for quantification of anti-spike interferon-γ (IFN-γ)-producing cells/106 peripheral blood mononuclear cells. Fifty patients (83.0%) were on immunotherapy alone, whereas 10 patients (7%) were on chemo-immunotherapy. We analyzed separately patients on immunotherapy and patients on chemo-immunotherapy. The median T-cell response at 6 months was significantly lower than that measured at 3 weeks after vaccination [50 interquartile range (IQR) 20-118.8 versus 175 IQR 67.5-371.3 IFN-γ-producing cells/106 peripheral blood mononuclear cells; P < 0.0001]. The median reduction of immunoglobulin G concentration was 88% in SARS-CoV-2-naive subjects and 2.1% in SARS-CoV-2-experienced subjects. SARS-CoV-2 NT Ab titer was maintained in SARS-CoV-2-experienced subjects, whereas a significant decrease was observed in SARS-CoV-2-naive subjects (from median 1 : 160, IQR 1 : 40-1 : 640 to median 1 : 20, IQR 1 : 10-1 : 40; P < 0.0001). A weak correlation was observed between SARS-CoV-2 NT Ab titer and spike-specific IFN-γ-producing cells at both 6 months and 3 weeks after vaccination (r = 0.467; P = 0.0002 and r = 0.428; P = 0.0006, respectively). Our work highlights a reduction in the immune response in cancer patients, particularly in SARS-CoV-2-naive subjects. Our data support administering a third dose of COVID-19 vaccine to cancer patients treated with programmed cell death protein 1/programmed death-ligand 1 inhibitors. •Median spike-specific T-cell response at 6 months was lower compared with 3 weeks after vaccine in SARS-CoV-2-naive subjects.•Median reduction of SARS-CoV-2-specific immunoglobulin G concentration was 88% in SARS-CoV-2-naive subjects.•The SARS-CoV-2 neutralizing activity was maintained stable in subjects with previous COVID-19.•No COVID-19 cases were documented throughout the period of study.